Dietary Supplementation of a Live Yeast Product on Dairy Sheep Milk Performance, Oxidative and Immune Status in Peripartum Period - Mavrommatis, Alexandros; Mitsiopoulou, Christina; Christodoulou, Christos A.; Karabinas, Dimitris; Nenov, Valentin; Zervas, George; Tsiplakou, Eleni (My University, 2020)
This study evaluated the dietary administration of Saccharomyces cerevisiae live yeast on milk performance and composition, oxidative status of both blood plasma and milk, and gene expression related to the immune system of lactating ewes during the peripartum period. Chios ewes were fed either a basal diet (BD) (Control, n = 51) or the BD supplemented with 2 g of a live yeast product/animal (ActiSaf, n = 53) from 6 weeks prepartum to 6 weeks postpartum. Fatty acid profile, oxidative, and immune status were assessed in eight ewes per treatment at 3 and 6 weeks postpartum. The β-hydroxybutyric acid concentration in blood of ActiSaf fed ewes was significantly lower in both pre- and postpartum periods. A numerical increase was found for the milk yield, fat 6% corrected milk (Fat corrected milk (FCM6%)), and energy corrected milk yield (ECM) in ActiSaf fed ewes, while daily milk fat production tended to increase. The proportions of C15:0, C16:1, C18:2n6t, and C18:3n3 fatty acids were increased in milk of ActiSaf fed ewes, while C18:0 was decreased. Glutathione reductase in blood plasma was increased (p = 0.004) in ActiSaf fed ewes, while total antioxidant capacity measured by 2,2'-Azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) method was decreased (p < 0.001). Higher ABTS values were found in the milk of the treated group. The relative transcript levels of CCL5, CXCL16, and IL8 were suppressed, while that of IL1B tended to decrease (p = 0.087) in monocytes of ActiSaf fed ewes. In conclusion, the dietary supplementation of ewes with S. cerevisiae, improved the energy utilization and tended to enhance milk performance with simultaneous suppression on mRNA levels of pro-inflammatory genes during the peripartum period.
Keywords: Antioxidant; Cytokines; Energy; Ewes; Livestock; Saccharomyces cerevisiae